Minimally invasive plate osteosythesis of fractures of the radius and ulna in a primate - Tong, K.; Guiot, L. P. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
A 25-year-old female mandrill (Mandrillus sphinx - a primate and part of the Old World monkey group) was presented with a mildly comminuted, diaphyseal, radial fracture associated with a transverse ulnar fracture. Minimally invasive plate osteosynthesis techniques were used to achieve fixation of both the radial and the ulnar fractures. First, closed fracture reduction was achieved with a distraction frame consisting of a motorized circular external skeletal fixator. Next, dual percutaneous radio-ulnar plating was performed using a 2.7 limited-contact dynamic compression plate on the cranial aspect of the radius and two stacked 2.0/2.7 veterinary cut-to-length plates on the lateral aspect of the ulna. Uncomplicated recovery was observed with a complete return to normal activity three months postoperatively. Fracture healing was documented at four weeks, clinical union at 14 weeks, and callus remodelling at 24 weeks postoperatively. This report demonstrates the feasibility of minimally invasive plate osteosynthesis in a primate and shows the adaptability of this technique across mammalian species.
Keywords: Minimally invasive plate osteosynthesis; MIPO; primate; radius; ulna; fracture; antebrachium